2002
DOI: 10.1136/vr.151.7.199
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of temperature, moisture, pH and bacteria in straw bedding, and faecal consistency, cleanliness and mastitis in cows in four dairy herds

Abstract: A study of four dairy farms showed that much of the straw stored for bedding was too wet (over 15 per cent moisture content). Most of the beds, including their top surfaces, were damp (above 75 per cent relative humidity). The temperature of the surface of most of the straw beds was related to the air temperature, many being below 15 degrees C, but below the surface the temperatures of most beds reached between 15 degrees C and 45 degrees C within about a week of their being renewed. Bacterial counts also reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 15 publications
6
73
1
1
Order By: Relevance
“…Veissier et al (2004) reported a tendency for soiling to increase as the number of stall beds per cow decreased. The farm with the cleanest cows had the least mastitis (Ward et al, 2002). Our study found no difference in SCC by bed type.…”
Section: Cow Hygienecontrasting
confidence: 30%
“…Veissier et al (2004) reported a tendency for soiling to increase as the number of stall beds per cow decreased. The farm with the cleanest cows had the least mastitis (Ward et al, 2002). Our study found no difference in SCC by bed type.…”
Section: Cow Hygienecontrasting
confidence: 30%
“…Work carried out by Blowey (1999) and a study by Ward et al (2002) have established that a relationship exists between bacterial numbers within bedding materials and the incidence of mastitis infections within the herd. A further study by Rendos et al (1975) identifies similar links, as found within this study, between bedding and bacteria numbers, although their study was carried out upon different bedding materials.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Rendos, Eberhart & Kesler (1975) identified that different bedding materials influenced the types and numbers of bacteria within such materials whilst a later study by Ward, Hughes, Faull, Cripps, Sutherland & Sutherst (2002) studied the effects of straw bedding upon the incidence of mastitic infections from environmental pathogens. The aim of this study, however, is to use three different bedding materials sand, sawdust and straw to examine the relationship between the bacterial numbers within the bedding material and the bacterial numbers found upon the teats within each herd.…”
Section: Introductionmentioning
confidence: 99%
“…Strawbedded yards provide a better environment for animal's welfare but a different environment for pathogens than the bedding of cubicles (Baars and Barkema, 1997). For example, if straw moisture content is too high, this can result in a rapid increase in the temperature of the bedding and an increased risk of Escherichia coli and Streptococcus uberis infections (Ward et al, 2002). The risk of mastitis from environmental pathogens has been found to be higher in straw-bedded yards compared with cubicle housing (Krutzinna et al, 1996;Weller and Bowling, 2000) and average SCC is higher in non-cubicle barns (Baars and Smolders, 2004).…”
Section: Farm Systems and Breedsmentioning
confidence: 99%